The Effect of Perceived Organizational Support (POS) On Employee Engagement, with Job Satisfaction as a Mediation Variable - Saibun Hamdi Dalimunthe; Nefi Darmayanti; Rahmi Lubis (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to analyze the effect of Perceived Organizational Support (POS) on Employee Engagement, with Job Satisfaction as a mediating variable. The phenomenon of low employee engagement in organizations highlights the importance of organizational support and job satisfaction as key factors in enhancing employees' involvement in their work. This research adopts a quantitative approach using Structural Equation Modeling (SEM), involving respondents from employees at PT X. The results show that POS has a positive and significant direct effect on employee engagement, with a coefficient value of 0.266 and a p-value of 0.017. Additionally, POS significantly affects job satisfaction with a coefficient of 0.793 and a p-value of 0.000. Job satisfaction also has a significant direct influence on employee engagement with a coefficient of 0.270 and a p-value of 0.020. The indirect effect of POS on employee engagement through job satisfaction is recorded at 21.4%, while the direct effect is higher at 26.6%, indicating that job satisfaction partially mediates the relationship. These findings emphasize that, in addition to the direct effect, job satisfaction plays a partial mediating role in the relationship between organizational support and employee engagement. This research offers practical insights for organizations to enhance engagement through improved support and job satisfaction strategies.